Study on the effects of gap forcing at two-way-stop controlled intersections using stimulation - Ladaga, Alex S.
Most methods involving estimation of capacities and delays of unsignalized intersections are based on Simple Gap Acceptance methods which assumes that major streams are not affected by minor streams. This means that in a simple two stream case the major stream cannot experience any delay while the minor stream have to evaluate first the gaps available in the major stream before it can depart. In this study, a simulation program is used to eliminate the usual problems encountered while doing actual surveys on capacities and delays of unsignalized intersection. The program takes into account the gap forcing that is common among drivers and examines its effects not only on the minor stream but on the major stream as well. A comparison between simulated data and the observed data using t-test shows tat the actual data can be predicted using the simulation program. The program is ten used to examine the behaviors of delays and capacities by varying the inputs of the following parameters; follow-on-time, and the number of left turns both from the minor and major legs. The author found out that capacities and delays are highly affected by these parameters that led to some important discussions on issues relating to delay and capacity estimation methods and warrants used for signalization.